Análise comparativa das propriedades físicas, químicas e ópticas de microesferas do tipo IB comerciais e fabricadas a partir da cinza da casca de arroz - Teixeira, Ingrid Machado (2025)
The increasing generation of agro-industrial waste poses environmental challenges that demand sustainable solutions. Rice husk, a byproduct of the rice production chain, accounts for about 20% of the grain's weight and, when burned, produces an ash rich in silica (SiO2), which can be reused in glass production. In this context, the present study proposes the manufacturing of Type IB glass microspheres from glass produced with rice husk ash (RHA), in accordance with the criteria established by the Brazilian standard. The objective is to compare their physical, chemical, and optical properties with those of comercial microspheres with similar characteristics. The methodology includes the production of glass in a high-temperature furnace (1500 °C), grinding and particle size separation of the fragments, followed by spheroidization using the horizontal flame method. The produced glass was evaluated for optical transparency in the visible spectrum and refractive index, and the obtained microspheres were characterized for morphology, particle size, density, chemical composition, resistance to acid attack, resistance to CaCl2, and retroreflectivity at a 15-meter geometry. The research aimed to validate the use of RHA as an alternative source of silica for application in road surface marking, contributing to the reuse of agricultural waste and the reduction of sand mineral extraction. The results highlighted the performance of RHA microspheres compared to commercial ones, proving their feasibility for industrial-scale production, with positive implications for environmental sustainability and technological innovation in materials for road infrastructure.